Are Fluctations In Energy Consumption Transitory Or Permanent? Evidence From A Fourier Adf Unit Root Test - Alper, Ali Eren (European Scientific Journal, ESJ, 2016)
This study analysis the stationarity of energy demand for 30 countries with annual data between 1960-2013 using the per capita energy consumption data acquired from kilogram petrol equivalent value. The per capita energy demand stationarity analysis is examined with the Fourier Augmented Dickey Fuller unit root test. The basic feature of the used econometric method is to include the unknown structural breaking features of the per capita energy demand to the analysis. The analysis results show that the energy demand are not stationary in Australia, Austria, Belgium, Brazil, Canada, China, Denmark, Finland, France, Germany, Greece, Iceland, India, Israel, Italy, Japan, South Korea, Mexico, Holland, New Zealand, Norway, Poland, Portugal, Spain, Sweden, Turkey, England and USA, so that the energy demand management policies have lasting and long term effects in these countries. It has been determined that the per capita energy demand series of the Czech Republic and South Africa are stationary and the energy demand policies in these countries won’t create long lasting effects but the energy demand predictions can be made by benefiting from the previous data of the energy demand.